2010
DOI: 10.1111/j.1464-410x.2009.08852.x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal protein expression in the corpus cavernosum impairs erectile function in type 2 diabetes

Abstract: they were then compared with rats that received a normal diet (ND). RESULTSHyperglycaemia and dyslipidaemia were induced in HFD + STZ rats, suggesting that T2D was established. The rats with T2D had associated ED, as both nonadrenergic noncholinergic-mediated corporal relaxation and increased ICP by cavernous nerve stimulation were significantly attenuated compared to the ND group. Western blot analysis revealed diabetes-associated lower expression of endothelial and neuronal nitric oxide synthase (e and nNOS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 24 publications
(29 reference statements)
2
40
0
Order By: Relevance
“…A growing body of evidence indicates that the erectile tissue of diabetic men and experimental type 1 and 2 diabetes animals manifests an inability to relax in response to the activation of nerves or the endothelium. 10,31,34,35) It is well known that normal erectile function is a hemodynamic neurovascular process involving relaxation of the corpus cavernosum. Although several vasodilators have been implicated in the erectile response, including vasoactive intestinal peptides, prostaglandin, and acetylcholine, the principal neurotransmitter for penile erection is NO, which is produced by the endothelium of the arteries of the penis and nitrergic neurons with the help of endothelial and neuronal NOS in response to sexual stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of evidence indicates that the erectile tissue of diabetic men and experimental type 1 and 2 diabetes animals manifests an inability to relax in response to the activation of nerves or the endothelium. 10,31,34,35) It is well known that normal erectile function is a hemodynamic neurovascular process involving relaxation of the corpus cavernosum. Although several vasodilators have been implicated in the erectile response, including vasoactive intestinal peptides, prostaglandin, and acetylcholine, the principal neurotransmitter for penile erection is NO, which is produced by the endothelium of the arteries of the penis and nitrergic neurons with the help of endothelial and neuronal NOS in response to sexual stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…5,7) Increasing evidence also indicates that diabetic ED also results from downregulation of the NO-cGMP signaling in the corpora cavernosum, including impaired NOS activity, low levels of NO and cGMP, and deficient activity of cGMP-dependent kinase. [8][9][10] It is a remedy for diabetic ED to preserve or strengthen the activity of the NO-cGMP pathway. At present, inhibitors of phosphodiesterase type 5 (PDE5) are the most effective oral drugs.…”
mentioning
confidence: 99%
“…As the downstream signaling of both NE and ET, RhoA/ROCK axis was found to be upregulated in diabetic animals as well. The expression of ROCK1, but not ROCK2, was significantly increased in penile tissues from different diabetic animal models, 4,83,84 indicating that ROCK1 is involved in diabetic ED. Furthermore, Angulo et al 101 demonstrated that diabetes causes hypercontractility of human cavernous tissue by a mechanism involving overactivity of PKC.…”
Section: Contractile Signaling and Edmentioning
confidence: 93%
“…84 Sullivan et al 26 reported a significant increase in ET B receptor binding sites in cavernous tissue of diabetic rabbits. As the downstream signaling of both NE and ET, RhoA/ROCK axis was found to be upregulated in diabetic animals as well.…”
Section: Contractile Signaling and Edmentioning
confidence: 99%
See 1 more Smart Citation